Mindful sitting - Fong, Hin Wai (2018)
With the increasingly prevalent use of technology, humans of the 21st century lead their daily lives in a manner that is vastly different from humans of previous centuries. Unlike our highly active ancestors, the movement seems to be missing from our increasingly sedentary lifestyle. One stark difference between us and our ancestors will be the prolonged sitting hours in our daily lives with little changes in posture. As such people, today experience back aches and pain due to prolonged muscle strains on the body caused by long hours of sitting without changing postures or incorrect postures.